THE STUDY OF KASHKADARYO FOLK EPICS AS AN OBJECT OF LINGUOCULTURAL RESEARCH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article reveals the principles of analyzing, from a linguocultural perspective, such units regarded as an integral part of folk culture as ethnographisms, phraseological units, similes and metaphors, paremiological, onomastic, and precedent units, as well as praises, wishes and curses, terms of endearment, euphemisms and dysphemisms, and beliefs employed in the texts of Qashqadaryo folk epics, and elucidates their role in the national language, history, and culture.